Ultrasonic Nakagami Imaging of High-intensity Focused Ultrasound-induced Thermal Lesions in Porcine Livers: Ex Vivo Study. (September 2018) - Huang, Sheng-Min; Liu, Hao-Li; Li, Dai-Wei; Li, Meng-Lin
High-intensity focused ultrasound (HIFU) has demonstrated the capacity to be used for local thermal ablation in clinical surgery; however, relying solely on conventional ultrasound B-mode imaging to monitor HIFU thermal ablation and determine ablation levels remains a challenge. Here, we experimentally demonstrate the ability to use Nakagami imaging to monitor HIFU-induced thermal lesions in porcine livers ex vivo. Ultrasonic Nakagami imaging has been proven to be able to characterize tissues with different scatterer concentrations and distributions. The pathological sections from HIFU thermally ablated porcine liver tissues reveal that normal and denatured tissues significantly differ in scatterer concentration and distribution. Therefore, we believe that Nakagami imaging can be used to monitor thermal ablation by tracing Nakagami parameter changes in liver tissues. The ex vivo porcine liver experiments were performed using a homemade HIFU device synchronized with a commercial diagnostic ultrasound scanner to obtain the ultrasound envelope data before and after thermal ablation. These data were used to evaluate the performance of thermal lesion characterization using Nakagami imaging and were compared with those derived from conventional B-mode imaging. Experimental results showed that Nakagami imaging can be used to identify thermal lesions, which are difficult to visualize using conventional B-mode imaging because there is no apparent bubble formation. In cases with apparent bubble formation, Nakagami imaging could provide a more accurate estimation of lesion size and position. In addition, the Nakagami imaging algorithm is characterized by low computational complexity, which means it can be easily integrated as postprocessing for existing array imaging systems.